High-fat diet is associated with endotoxemia and low-grade inflammation - Shrestha, Umid Kumar (Nepal Journal of Medical Sciences, 2012)
DOI: http://dx.doi.org/10.3126/njms.v1i2.6600 Nepal Journal of Medical Sciences. 2012;1(2): 62-3